Al3+ ACCEPTORS AND THE OPTICAL PROPERTIES OF Bi12SiO20:Cr+Al: Al3+ ACCEPTORS AND THE OPTICAL PROPERTIES OF Bi12SiO20:Cr+Al - Petkova, Petya; Vasilev, Petko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Absorption measurement is taken in the visible spectral region (650 - 850 nm). The dopants Cr3+ and Al3+ ions occupy the tetrahedral sites in the crystal lattice of doped sillenite. The electron transitions in Cr3+ are presented in the case of Bi12SiO20:Cr and Bi12SiO20:Cr+Al. The total cross-section of combined chromium-aluminium absorption structure and the spin-orbit coupling energy of Cr3+ are calculated.